1994
DOI: 10.1007/bf02032890
|View full text |Cite
|
Sign up to set email alerts
|

The expression of parathyroid hormone-related protein in human breast cancer with skeletal metastases

Abstract: The relationship between the expression of parathyroid hormone-related protein (PTHrP) by breast cancer and skeletal metastases, was investigated using a monoclonal antibody against human PTHrP (4B3). The immunohistochemical localization of PTHrP was studied in sections of formalin-fixed, paraffin-embedded tissues from 28 breast cancers obtained surgically between 1980 and 1985. Of the 28 patients, 12 developed skeletal metastases, 8 developed lung metastases, and the other 8 were alive and disease-free at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 18 publications
3
33
0
Order By: Relevance
“…At least four other studies have confirmed these percentages, and one of these has demonstrated immunoreactive PTHrP within the cytoplasm of lobular and ductal epithelial cells in normal and fibrocystic breast tissues (Bundred et al 1991, Liapis et al 1993, Kohno et al 1994. Furthermore, 65-92% of hypercalcaemic breast cancer patients (with and without bone metastasis) had detectable plasma PTHrP concentration by radioimmunoassay similar to those documented in patients with HHM due to non-breast tumours (Bundred et al 1991, Grill et al 1991.…”
Section: Hhm Vsmentioning
confidence: 83%
“…At least four other studies have confirmed these percentages, and one of these has demonstrated immunoreactive PTHrP within the cytoplasm of lobular and ductal epithelial cells in normal and fibrocystic breast tissues (Bundred et al 1991, Liapis et al 1993, Kohno et al 1994. Furthermore, 65-92% of hypercalcaemic breast cancer patients (with and without bone metastasis) had detectable plasma PTHrP concentration by radioimmunoassay similar to those documented in patients with HHM due to non-breast tumours (Bundred et al 1991, Grill et al 1991.…”
Section: Hhm Vsmentioning
confidence: 83%
“…In other words, tumour-derived PTHrP acts as a circulating hormone like parathyroid hormone and induces hypercalcaemia. Recently, a series of studies has indicated that PTHrP is commonly expressed in breast cancer and that a higher expression of PTHrP may induce bone metastasis (Southby et al, 1990;Powell et al, 1991;Bundred et al, 1992;Vargus et al, 1992;Bouizar et al, 1993;Kohno et al, 1994a;Kohno et al, 1994b). It is conceivable that the PTHrP secreted by breast cancer cells, which exist in bone marrow, may act as a paracrine effector on osteoclasts, resulting in osteolytic involvement.…”
mentioning
confidence: 99%
“…Its expression by breast cancer cells appears to increase when the tumor cells metastasize to bone. For example, it has been detected by immunohistochemistry (Powell et al 1991, Kohno et al 1994 and in situ hybridization (Vargas et al 1992) in 80-90% of breast cancer metastases in bone, compared with only 38% in lung (Kohno et al 1994) and 17% (Powell et al 1991) in other non-bone sites. These findings suggest that PTHrP expression by breast cancer cells increases when they metastasize to bone and support a major potential role for tumor-produced PTHrP to mediate the increased bone resorption around osteolytic breast metastases.…”
Section: Pthrp and Bone Metastasismentioning
confidence: 99%